(untitled) (E Global Congress, 2025)
Today, foreign investments are recognized as a crucial factor in the economic growth of countries within the global economy. Foreign capital helps create new jobs, introduce technologies, increase economic efficiency, and strengthen integration between countries. At the same time, mechanisms ensuring financial security and risk reduction for investors, including insurance systems, play a significant role in the process of attracting investments. These factors increase investor confidence and enable them to allocate their funds safely and effectively.